Netflix Organizational Culture - An Environment to Support the Career Development of Employees in a Socially Responsible Company - Todorova, Ana (Research Papers, 2020)
Internal corporate social commitment also refers to the long-term consequences of the company's relations with its employees, namely their careers. Netflix has built a unique culture that supports the careers and development of its employees, in ways that are interesting not only because they are not traditional, but also because they are extremely relevant to its specific context. By affirming the adherence to the values of the organization in each situation, the company creates for people an environment in which they have clarity and certainty about how to act properly. The adopted policy ensures fair and transparent treatment of employees in terms of remuneration. The organization sees its commitment to employee training and development in providing them with "great colleagues and challenges to work with" and protecting people from mediocre colleagues or jobs that they lack challenges, because these are the real obstacles to the development of people's skills. By affirming giving honest feedback as a must for any behavior, Netflix encourages people to meet high standards of performance and develop their skills. The policies of "context, not control" and "freedom and responsibility" give everyone the opportunity to show their abilities and creativity and to upgrade their professionalism.
Keywords: Corporate social responsibility; Human resources management; Internal corporate social responsibility; Corporate citizen; Training and development; Career development; Organizational culture; Organizational values; Career